Pengembangan Media Pocket Book Guna Melatih Keterampilan Menulis Huruf Tegak Bersambung 2 SD - Aisyah Bitis Rohmatulloh; Ratih Asmarani (Prodi PGSD Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2023)
Writing ability is the ability to convey messages to others in writing, but there are still many problems with writing skills, one of which is writing cursive letters. The problems that occur are, some students still have difficulty in arranging and connecting concatenated letters, some students have difficulty arranging loose letters, and some students are tired of writing too many cursive letters. This study aims to provide education for children in writing cursive letters through the development of Pocket Book media. This study uses the R&D (Research and Development) research method and uses the ADDIE development model. There are 5 Development Processes that have been implemented in this research, namely: 1) Analysis, 2) Design, 3) Development, 4) Implementation, 5) Evaluation. The Pocket Book media assessment was carried out by media, material, educator responses and student responses for grade 2 SDN Ceweng Jombang. The results of Pocket Book media development research show that the percentage obtained from media expert validators is 88.24% with a very valid and appropriate category for use, material expert validators are 85.29% in a very valid and suitable category for use. Furthermore, the results of trials or educators are 92% with a suitable category for use. The results of field trials with 17 students with a percentage of 91% with a very interesting category. Based on the results of the analysis, Pocket Book media is feasible to be used as a learning medium